Effect of L-Carnitine and Niacin addition on some blood parameters of fry Common Carp Cyprinus carpio: N. A. M. Al-Muslimawi and S. A. Al-Shawi - Al-Muslimawi, N. A. M. (The Iraqi Journal of Veterinary Medicine, 2016)
The present study was conducted in order to focus on the effect of the addition of Carnitine and Niacin on some blood serum parameters of Common Carp Cyprinus Carpio. 48 fish carp mean weight 44.13 gm were distributed randomly on four feeding treatments (12 fish each) with replicates (6 fish each) in 8 glass aquaria. Treatments were as follows: fish were fed on basic diet without any addition and conducted as control (T1); addition of 200 mg Carnitine/ Kg diet, (T2) addition of 28 mg Niacin/Kg diet (T3), addition of a mixture of 200 mg Carnitine and 28 mg Niacin/ Kg diet as (T4). The experiment was conducted for 70 days and the results showed an increase in the Cholesterol concentration of T1 (187.6 mg/ 100 ml) and differed significantly (P<0.05) from T2 (163.95 mg / 100 ml), T3 (157.6 mg/ 100 ml) and T4 (162.43 mg / 100 ml) where they did not differ between them. Total protein Serum concentrations of T2 (5.11 mg/ dl), T3 (5.00 mg / dl) and T4 (5.07mg/dl) were not differ significantly but all differed significantly (P≤0.05) with T1 (4.07mg/ dl). Conclusion showed that fish fed on (200 mg Carnitine and 28 mg Niacin) had low serum cholesterol concentrations and high serum total protein